Predictors of Commercial Zapping during Live Prime-Time Television: An Observation-Based Study Identifies Factors That Drive TV Channel Switching - Dix, Steve; Phau, Ian (World Advertising Research Center, 2017)
Television advertising-avoidance research delivers a broad range of estimates for the extent of channel switching during advertising breaks (i.e., commercial zapping). The diverse methods likely contribute to the disparity in commercial-zapping estimates. This study implements a combined hidden-observation/survey approach and tests potential predictors of commercial zapping. The use of remote controls emerged as a significant driver of observed commercial zapping. Perceived clutter and advertising triggers emerged as significant predictors of reported commercial zapping. This study empowers media planners to determine prime-time advertising-audience erosion more accurately. Additionally, with a greater degree of confidence, advertisers can address factors that drive channel-switching behavior and dismiss factors that do not.